Diffuse Reduction of Spleen Density Is an Independent Predictor of Post-Operative Outcomes After Curative Gastrectomy in Gastric Cancer: A Multi-Center Study - Huang, Yun-Shi; Chen, Xiao-Dong; Shi, Ming-Ming; Xu, Li-Bin; Wang, Su-Jun; Chen, Wei-Sheng; Zhu, Guan-Bao; Zhang, Wei-Teng; Shen, Xian (Frontiers in Oncology, 2020)
Objectives: The host immune system is one of the indispensable participants in its own antitumor function. Recent studies have demonstrated patients with diffuse reduction of spleen density (DROSD) had more severe immune dysfunction than without. The present study aimed to explore the association between spleen density and post-operative outcomes of patients after curative gastrectomy. Methods: From June 2014 to December 2015, we conducted a retrospective study to analyze pertinent clinical data from gastric cancer patients who underwent gastrectomy at the First and the Second Affiliated Hospital of Wenzhou Medical University. Spleen density was determined via computed tomography scans. Univariate and multivariate analyses were performed to determine the risk factors associated with post-operative outcomes after gastric cancer surgery. Results: 391 patients were included, of whom 96 (24.6%) were defined as having a diffuse reduction of spleen density based on diagnostic cutoff values (spleen density ≤ 43.89 HU). Multivariate analysis revealed diffuse reduction of spleen density as an independent risk factor for post-operative complications and 3-year survival. Conclusions: Spleen density can predict post-operative complications and 3-year survival in gastric cancer patients. As an imaging evaluation method, spleen density is a novel tool can be used in clinical as a prognostic predictor for patients with gastric cancer.